2017
DOI: 10.1002/gch2.201700095
|View full text |Cite
|
Sign up to set email alerts
|

A 25.1% Efficient Stand‐Alone Solar Chloralkali Generator Employing a Microtracking Solar Concentrator

Abstract: or where extending the power connection lines would not be economically justifiable. Besides its direct use for lighting, appliances, etc., stand-alone photovoltaic electricity can be utilized to generate a valuable chemical feedstock via electrochemical processes. They are the natural entry point for PV integration, as these processes specifically require direct electricity to operate. Their scalability, coupled with the possibility to modulate the load and possibly operate on-demand, facilitates the implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…where j is the measured current density, in mA cm À2 ; E 0 cell the cell working potential (2.188 V), given the negligible effect of the mixing contribution; 26 h Faraday the cell faradaic efficiency; P solar the solar power input (GHI for 4SHJ and 5SHJ; DNI for MJ cells coupled with concentration), in mW cm À2 , retrieved from the LESO-SB weather station online platform. It was estimated that the condence interval for the experimental SCEs was AE7.1%.…”
Section: Scementioning
confidence: 99%
See 2 more Smart Citations
“…where j is the measured current density, in mA cm À2 ; E 0 cell the cell working potential (2.188 V), given the negligible effect of the mixing contribution; 26 h Faraday the cell faradaic efficiency; P solar the solar power input (GHI for 4SHJ and 5SHJ; DNI for MJ cells coupled with concentration), in mW cm À2 , retrieved from the LESO-SB weather station online platform. It was estimated that the condence interval for the experimental SCEs was AE7.1%.…”
Section: Scementioning
confidence: 99%
“…The latter ndings are consistent with other studies previously reported employing GaAs solar cells and solar concentration. 26 It is worth stressing that for a PV technology to ensure stability of operation, it has to full the condition: V MPP > E 0 cell + h, where h corresponds to the reaction overpotentials. In order to maximize the SCE throughput, the electrochemical cell must then be tailored to target the currentload match and to ensure a V OP lower than V MPP .…”
Section: Scementioning
confidence: 99%
See 1 more Smart Citation
“…The angular acceptance was validated over AOIs of +/-40° (limited by mechanical constraints that have been lifted since then) with optical efficiencies > 80% of the cosine law (Fig 2b-c). As an application example, the device was used to power an off-grid chloralkali electro-chemical reactor, taking advantage of the MJ cell's large V oc > 3V [9]. Recently, Ito et al published a detailed analysis of a very similar design, demonstrating efficient focusing up to 55° AOI, nearly 30% module efficiency vs direct irradiance, and a 32% increase of power generation with respect to conventional Si cells on a sunny day [10].…”
Section: Insolight's Lab Prototype (2016)mentioning
confidence: 99%
“…While MTC of commercial standard CPV modules is typically between 65% and 75%, miniaturized modules have shown MTC in the range 71%–87% 10 . Consequently, micro‐CPV modules have already demonstrated high efficiency (>35%) with a record of 41.7% 11–18 . A summary of existing high‐performance micro‐CPV modules is reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%